Phytochemical profiling of antimicrobial and potential antioxidant plant: Nepeta cataria - Nadeem, Ali; Shahzad, Hira; Ahmed, Bashir; Muntean, Tudor; Waseem, Maaz; Tabassum, Aisha (Frontiers in Plant Science, 2022)
Traditional and phytochemical studies have confirmed the richness and diversity of medicinal plants such as Nepeta cataria (N. cataria), but more studies are needed to complete its metabolite profiling. The objective of this research was to enhance the metabolomic picture and bioactivity of N. cataria for better evaluation. Phytochemical analysis was performed by bio-guided protocols and Gas Chromatography Mass Spectrometry (GC/MS). For this, solvents like methanol, ethanol, water, acetone, and hexane were used to extract a wide number of chemicals. Antibacterial analysis was performed by 96 well plate test, Kirby Bauer’s disc diffusion method, and resazurin microdilution test. Antioxidant activity was determined by the DPPH assay and radical scavenging capacity was evaluated by the oxygen radical absorbance capacity (ORAC) assay. GC/MS analysis revealed a total of 247 identified and 127 novel metabolites from all extracts of N. cataria. Water and acetone extracts had the highest identified metabolites (n=79) whereas methanol extract was highest in unidentified metabolites (n=48). The most abundant phytochemicals in methanol extract were 1-Isopropylcyclohex-1-ene (concentration = 27.376) and Bicyclo [2.2.1] heptan-2-one (concentration = 20.437) in ethanol extract it was 9,12,15-Octadecatrienoic acid (concentration = 27.308) and 1-Isopropylcyclohex-1-ene (concentration = 25.854). An abundance of 2 methyl indoles, conhydrin, and coumarin was found in water extracts; a good concentration of eucalyptol was found in acetone extract and 7,9-Di-tert-butyl-1-oxaspiro is the most abundant phytochemicals in hexane extracts. The highest concentration of flavonoids and phenols were identified in hexane and methanol extracts, respectively. The highest antioxidant potential (DPPH assay) was observed in acetone extract. The ethanolic extract exhibited a two-fold higher ORAC than the methanol extract. This examination demonstrated the inhibitory effect against a set of microbes and the presence of polar and non-polar constituents of N. cataria. The results of the present study provide a safe resource for the development of food, agriculture, pharmaceutical, and other industrial products upon further research validation.